Textbook outcome in ovarian cancer and its impact on survival: comparative study - Silvia Carbonell-Morote; Alvaro Arjona-Sánchez; Pedro Antonio Cascales-Campos; Alida González-Gil; Gonzalo Gomez-Dueñas; Elena Gil-Gómez; Iban Caravaca-García; Veronica Aranaz; Francisco Javier Lacueva; José Manuel Ramia (World Journal of Surgical Oncology)
Abstract Introduction Patients who achieve the textbook outcome (TO) present an uneventful postoperative course. Obtaining TO has also been related to better survival in oncological patients. Information about TO in patients with peritoneal carcinomatosis from ovarian cancer who undergo surgery is very scarce. Our objective was investigate TO in patients with carcinomatosis of ovarian origin who underwent interval surgery with or without HIPEC (TOOC) and its impact on survival. Methods A multicenter study was performed between 2010 and 2015. Inclusion criteria were > 18 years old, with ovarian cancer and peritoneal carcinomatosis, who underwent scheduled surgery after response to neoadjuvant therapy. The criteria to establish TOOC were no major complications, no mortality, non-prolonged stay (p75:10 days), complete cytoreduction (CC-0), and no readmission. Results 365 patients were included, and TOOC was achieved in 204 (55.9%) patients. CC-0 cytoreduction was obtained in 312(85.5%). 7 patients (1.9%) died. 71 (19.5%) presented major complications (≥ IIIa). The readmission rate was 9.3%, and 24.9% of the patients presented a prolonged stay. The parameter with most significant negative impact on achieving TOOC was length of stay. Multivariate analysis confirmed postsurgical PCI, age, HIPEC, and time of surgery in minutes as an independent factor of TOOC. Survival analysis showed that patients who achieved TOOC had better overall survival (41 months (24.5– 67) versus 27 months (14-48.2) (p < 0.0001). Conclusion TO is an easy and valuable management tool for evaluating and comparing results obtained at different centers after surgery for peritoneal carcinomatosis of locally advanced ovarian cancer. Achieving TOOC benefits overall survival.